Bacteriocin Producing Streptococcus agalactiae Strains Isolated from Bovine Mastitis in Brazil - João Ricardo Vidal Amaral; Rommel Thiago Jucá Ramos; Fabrício Almeida Araújo; Rodrigo Bentes Kato; Flávia Figueira Aburjaile; Siomar de Castro Soares; Aristóteles Góes-Neto; Mateus Matiuzzi da Costa; Vasco Azevedo; Bertram Brenig; Selma Soares de Oliveira; Alexandre Soares Rosado (Microorganisms, 2022)
Antibiotic resistance is one of the biggest health challenges of our time. We are now facing a post-antibiotic era in which microbial infections, currently treatable, could become fatal. In this scenario, antimicrobial peptides such as bacteriocins represent an alternative solution to traditional antibiotics because they are produced by many organisms and can inhibit bacteria, fungi, and/or viruses. Herein, we assessed the antimicrobial activity and biotechnological potential of 54 Streptococcus agalactiae strains isolated from bovine mastitis. Deferred plate antagonism assays revealed an inhibition spectrum focused on species of the genus Streptococcus—namely, S. pyogenes, S. agalactiae, S. porcinus, and S. uberis. Three genomes were successfully sequenced, allowing for their taxonomic confirmation via a multilocus sequence analysis (MLSA). Virulence potential and antibiotic resistance assessments showed that strain LGMAI_St_08 is slightly more pathogenic than the others. Moreover, the mreA gene was identified in the three strains. This gene is associated with resistance against erythromycin, azithromycin, and spiramycin. Assessments for secondary metabolites and antimicrobial peptides detected the bacteriocin zoocin A. Finally, comparative genomics evidenced high similarity among the genomes, with more significant similarity between the LGMAI_St_11 and LGMAI_St_14 strains. Thus, the current study shows promising antimicrobial and biotechnological potential for the Streptococcus agalactiae strains.